2020
DOI: 10.3389/fpsyg.2020.620042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coronavirus Disease 2019 (COVID-19) on Elite Spanish Student-Athletes’ Perception of the Dual Career

Abstract: The aim of the present research was to assess elite student-athletes’ perception of the dual career during the lockdown caused by the coronavirus disease 2019 (COVID-19) pandemic, compared with a group of elite student-athletes who could develop their dual career under normal conditions. A total of 150 elite athletes who were also undergraduate or postgraduate students self-completed the “Perceptions of dual career student-athletes (ESTPORT)” questionnaire. From them, 78 did it during the mandatory lockdown pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Specifically, by delving deeper into the content unit on the student-athlete, the participants of the focus groups envisaged the recognition of S-As status for both elite athletes and athletes committed to an organized sport within their respective sport federations, and engaged in demanding training and competitions independently from the competition level. In fact, both elite and sub-elite athletes engage in sports with demanding training and competition schedules, which challenge them to combine their DC paths, especially in the absence of academic and/or sport DC support, lack of flexible academic and sport schedules, and in the presence of long distances between the university and the sport venues [25,26].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, by delving deeper into the content unit on the student-athlete, the participants of the focus groups envisaged the recognition of S-As status for both elite athletes and athletes committed to an organized sport within their respective sport federations, and engaged in demanding training and competitions independently from the competition level. In fact, both elite and sub-elite athletes engage in sports with demanding training and competition schedules, which challenge them to combine their DC paths, especially in the absence of academic and/or sport DC support, lack of flexible academic and sport schedules, and in the presence of long distances between the university and the sport venues [25,26].…”
Section: Plos Onementioning
confidence: 99%
“…Conversely, in countries with no DC policies in place or tied to traditional didactics, severe legal constraints and university administrative rules uphold face-to-face education, exacerbating the difficulties of S-As. However, during the recent COVID-19 pandemic lockdown, the European HEIs were confronted with a prompt and agile response to continue their academic activities, the adoption of remote methods [25,65]. At present, distance learning is no longer a new concept, and HEIs developed sustainable e-learning systems including recorded lectures, which could be maintained to allow distance learning and academic flexibility, to guarantee future opportunities for an adequate support of S-As and other atypical students [66].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies in athletes published to date have been conducted during the lockdown period ( Abenza-Cano et al, 2020 ; Corsini et al, 2020 ; Jukic et al, 2020 ; McGuine et al, 2021 ; Samuel et al, 2020 ; Taku and Arai, 2020 ) and some of them, in the final period, when athletes were very close to reactivate their sporting activity ( Pillay et al, 2020 ), but there is little scientific evidence on the consequences perceived by athletes in the post-lockdown period and the impact it may be having on their physical and mental health and quality of life, taking into account the proximity of the Tokyo 2021 Olympic Games. Attending this need in the scientific literature, the main objectives in this study were (a) to determine the effects of the COVID-19 health crisis on Spanish elite athletes related to (a.1) sports practice, (a.2) health, life quality, and performance perception, (a.3) emotional state in the current situation of post-lockdown as well as (b) to identify the profile of the athletes with the greatest difficulties in this period, to whom the necessary attention and help should be given.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it has been found that sports federations and other sports organizations should promote gender policies and create ad hoc programs to promote equality in all areas of sports [29,50]. In agreement with this, previous research studies have pointed out the importance of the social context and the need for stakeholder support to enable the holistic development of the female athlete [41,45], which allows not only their growth in sports, but also their educational progress with their inclusion in dual career programs [51,52], and the resulting employment success during and after their active careers [53,54]. These factors are essential for achieving the complete disappearance of the gender gap in sports [41,53].…”
Section: Plos Onementioning
confidence: 69%